Antibacterial honey (Medihoney(®)) for wound care of immunocompromised pediatric oncology patients - Simon, Arne (German Medical Science, 2006)
The physiologic process of wound healing is impaired and prolonged in paediatic patients receiving chemotherapy. Due to profound immunosuppression, wound infection can easily spread and act as the source of sepsis. Referring to in vitro studies, which confirmed the antibacterial potency of special honey preparations against typical isolates of nosocomially acquired wound infections (including MRSA and VRE) and considering the encouraging reports from other groups, Medihoney™ has now been used in wound care at the Department of Pediatric Oncology, Children's Hospital, University of Bonn for three years. Supplemented with exemplary clinical data from pediatric oncology patients, this presentation reviews the scientific background and our promising experience with Medihoney™ in wound care issues at our institution.